PENGARUH PELATIHAN KERJA, DISIPLIN KERJA DAN SELF-EFFICACY TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN GIANYAR - Nengah Landra; Gde Bayu Surya Parwita; Ida Ayu Made Pebryanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Performance is the result of work that is produced as a measure of the success of an agency in achieving the set targets. Employee performance can be affected by job training, work discipline and self-efficacy. Each of these factors are interconnected with each other, when employees often receive appropriate training, good employeediscipline and self- efficacy are well formed, the resulting performance will be good too. These three factors must work in a balance to create the employee performance expected by company. The research population was employees of the Gianyar Regency Social Service with a sampling techniqueusing a saturated sample technique, so the total population is the number of samples. The sample used was 40 respondents. The analytical tool used to test the hypothesis is multiple linear regression. The results showed that job training had a positive and significant effect on employee performance, work discipline had a positive and significant effect on employee performance, and self-efficacy had a positive and significant effect on employee performance. Further research can develop this research by using other variables which in theory have aninfluence on employee performance.